COVID-19: the gut to lung hypothesis - Natalia Skorzewska (University of New South Wales, 2020)
Increasingly COVID-19 is being recognised as a multisystem disease, with viral replication within the gastrointestinal tract now being well accepted. This article collates evidence pointing to possible gastrointestinal transmission as well as outlining possible mechanisms for intra-institutional or cruise ship spread, and explores the possible impact of gastrointestinal replication on disease course.